THE SINO – US RELATIONSHIP : STUDI KASUS KEBIJAKAN AMERIKA SERIKAT TERHADAP ONE CHINA POLICY - Arthur Wabiser, Yosias Marion (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
ABSTRACT Taiwan and china beginning conflict when the difference integrity of the two nations who desire full sovereignty to in a single nation and China making a policy of "one China policy" that is approved the two nations. when the United States established diplomatic relations with Taiwan, China considers Taiwan as a barrier Relations PRC and the United States, and in violation of the agreement "One China Policy". This research uses descriptive method, with the concept of Strategic ambiugity Keyword: China,Taiwan,US,One China policy,strategic ambiugity